Circadian regulation of the GLYCINE-RICH RNA-BINDING PROTEIN gene by the master clock protein CIRCADIAN CLOCK-ASSOCIATED 1 is important for plant innate immunity. (11th November 2022) - Gao, Min; Zhang, Chong; Angel, William; Kwak, Owen; Allison, Jessica; Wiratan, Linda; Hallworth, Amelia; Wolf, Julie; Lu, Hua
Abstract: Recent studies have demonstrated the importance of temporal regulation of pathogen defense by the circadian clock. However, our understanding of the molecular basis underlying this role of the circadian clock is still in its infancy. We report here the mechanism by which the Arabidopsis master clock protein CCA1 regulates an output target gene GRP7 for its circadian expression and function in pathogen defense. Our data firmly establish that CCA1 physically associates with the GRP7 promoter via the predicted CCA1-binding motif, evening element (EE). A site-directed mutagenesis study showed that while individual EE motifs differentially contribute to robust circadian expression of GRP7, abolishing all four EE motifs in the proximal GRP7 promoter disrupts rhythmicity of GRP7 expression and results in misalignment of defense signaling mediated by GRP7 and altered pathogen responses. This study provides a mechanistic link of the circadian regulation of an output gene to its biological function in pathogen defense, underscoring the importance of temporal control of plant innate immunity. Abstract : This research establishes a direct transcriptional control by the master clock regulatory protein CCA1 on a downstream target gene GRP7 for its circadian expression and function in pathogen defense.